A Permissive Theory of Territorial Rights. (9th February 2012) - Ypi, Lea
Abstract This article explores the justification of states' territorial rights. It starts by introducing three questions that all current theories of territorial rights attempt to answer: how to justify the right to settle, the right to exclude, and the right to settle and exclude with reference to a particular territory. It proposes a 'permissive' theory of territorial rights, arguing that the citizens of each state are entitled to the particular territory they collectively occupy, if and only if they are also politically committed to the establishment of a global political authority realizing just reciprocal relations. The article is developed by introducing some key features of the permissive theory and by explaining how such an account addresses the questions of settlement, exclusion and particularity in ways that significantly improve on existing rival accounts (most prominently: acquisition theories, legitimacy‐based theories and nationalist theories).